Pemberian ASI Ekslusif pada ibu menyusui diwilayah kerja Puskemas Umban Sari Pekanbaru - Lisvia Rose (STIKes Al-Insyirah Pekanbaru, 2018)
ABSTRAC Mother's Milk is an exclusive food for babies. The purpose of this study was to find out Exclusive Breastfeeding for Breastfeeding Mother in the Working Area of Umban Sari Pekanbaru Community Health Center. This research method is Analytical Cros Sektional Study by using questioner. This research method is Analysis Cros Sectional Study by using questioner. The population in this study all breastfeeding mothers with infants aged 6-12 months was 121 people, the total sample in this study total of 121 breastfeeding mothers with infants aged 6-12 months. Data analysis using Chi Square test. The results showed that 58.7% of mothers did not give Exclusive Breast Milk, related variables in which low-educated mothers with P value 0,000 were at risk 0.246 times (95% CI: 0.110-0.550) than mothers with higher education, with P value 0.767 no risk 0.892 times (CI: 95% POR = (0.418-1,904) feeding infants other than breastmilk than well-informed mothers, mothers who do not get support from families with P value 0.100 in exclusive breastfeeding more risk 1,843 times (95% CI: 0,887-3,832) than mothers who get support from family role Advice given in the form of improving health promotion or counseling by health workers at health center about breastfeeding procedure and breastfeeding excellence need to be improved, when mother visit to the health services of pregnant / lactating women accompanied by families so that health workers can explain me on the importance of breastfeeding for infants and the disadvantages of using breastmilk substitutes such as formula milk, tajin water, and others.